PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA SEBAGAI USAHA KECIL SELARAS DENGAN TATA RUANG WILAYAH KOTA PEKALONGAN - Esmara Sugeng; Listyo Budi Santoso (LPPM Universitas Pekalongan, 2011)
Vendors included in the category of small businesses, and also as an integral part of business which is the economic activity of society. Vendors have the position, potential and strategic role to realize the structure of the national economy that increasingly balanced by economic democracy Relative to the street hawkers as a small business need to be more empowered to take advantage of business opportunities and address challenges of economic development in the future. Arrangement of street vendors is not an easy task, because it involves the lives of many that can be said to reflect the life of